The interplay of Sufism and Sharī‛ah in Tayeb Salih’s work - Owoyemi, Musa Yusuf (Islamic Cultural Centre, London, 2013)
This article explores the literary work of the Sudanesc writer Tayeb Salih.Using the textual analysis method, it examines the interplay and tension that exist within the Islamic faith as it concerns its exoteric and esoteric aspects in the novella entitled The Wedding of Zein and Other Stories.The contention of Salih is that whilst the esoteric aspect of Islam (Sufism) portrays mercy, magnanimity and calmness for the people whose story he tells, the exoteric aspect (Shari'ah) portrays harshness, sadness and is a constant reminder of death, which stifles their enjoyment of this world.The contrast between these two aspects of Islam, as recanted by Salih, is the basis of analysis in this paper with relation to the everyday reality of Muslims in Africa.Whilst the people love the esoteric aspect of' Islam, mainly because of its understanding of their limitations as human beings and its focus on mercy over punishment, they dislike the exoteric aspect because of its aloofness and focus on punishment over mercy.They see the exoteric aspect as a necessary component of their society, which they cannot do without because of its function in some religious rites.Finally, the article opines that the novella of Salih is real in that it applies to many Muslim societies in Africa and amply depicts the daily struggle and tension between Sufism and Shari'ah.